2013
DOI: 10.1161/strokeaha.113.001943
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenesis in Experimental Stroke After Human Cerebral Endothelial Cell Transplantation

Abstract: Background and Purpose Despite the reported functional recovery in transplanted stroke models and patients, the mechanism of action underlying stem cell therapy remains not well understood. Here, we examined the role of stem cell-mediated vascular repair in stroke. Methods Adult rats were exposed to transient occlusion of the middle cerebral artery and 3 hours later randomly stereotaxically transplantated with 100K, 200K, or 400K human cerebral endothelial cell 6 viable cells or vehicle. Animals underwent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 49 publications
(47 reference statements)
2
80
0
Order By: Relevance
“…The failure of direct neuroprotection in stroke therapy has promoted a more holistic approach to treatment, taking into consideration the communication between different brain cell types and especially considering endothelial cells as a "neuroprotective organ" (Guo et al, 2008). In agreement, a recent study demonstrated the involvement of VEGF-A in endothelium-mediated neuroprotection after stroke (Ishikawa et al, 2013). In summary, our findings provide new insights on the benefits of candesartan and show that these benefits are mediated through orchestrated actions of multiple players, including endothelial VEGF-A and VEGF-B.…”
Section: Candesartan Induces a Prolonged Proangiogenic Effectmentioning
confidence: 88%
“…The failure of direct neuroprotection in stroke therapy has promoted a more holistic approach to treatment, taking into consideration the communication between different brain cell types and especially considering endothelial cells as a "neuroprotective organ" (Guo et al, 2008). In agreement, a recent study demonstrated the involvement of VEGF-A in endothelium-mediated neuroprotection after stroke (Ishikawa et al, 2013). In summary, our findings provide new insights on the benefits of candesartan and show that these benefits are mediated through orchestrated actions of multiple players, including endothelial VEGF-A and VEGF-B.…”
Section: Candesartan Induces a Prolonged Proangiogenic Effectmentioning
confidence: 88%
“…94 A recent study showed that endothelial cells transplanted into the brain promote vasculogenesis and enhance neurogenesis further providing support for this concept. 95 This neuroplasticity is important for meaningful functional recovery, but may be diminished by aging and other comorbidities. 93 There is emerging evidence that neuroplasticity and recovery after brain injury involve areas remote from the injury itself.…”
Section: Stroke and Neovascularizationmentioning
confidence: 99%
“…The study revealed death of RCMs through the conference of cell death signals from the ischemic brain to the heart. With the results gained from this study [14], Ghanekar and her colleagues address these findings and their clinical implications in this review paper. Considering the insular cortex is responsible for controlling heart rhythm, they assert that stroke in this region could result in arrhythmias or even sudden death.…”
Section: Cell Death Mechanisms Mediating Neurological Disorders As Thmentioning
confidence: 84%
“…Considering the insular cortex is responsible for controlling heart rhythm, they assert that stroke in this region could result in arrhythmias or even sudden death. The in vitro study also identified autophagy-related cell death signals could be responsible for cardiac failure following stroke [14], indicating that while stroke may initiate in one area, the damage can spread to the rest of the brain and possibly the heart. The presence of elevated levels of brain natriuretic peptide (BNP) and N-terminal-pro-brain natriuretic peptide (NT-proBNP) following ischemic stroke suggests the role of the kidney in stroke pathology.…”
Section: Cell Death Mechanisms Mediating Neurological Disorders As Thmentioning
confidence: 92%
See 1 more Smart Citation